Correlation and Regression Between Body Measurements and Body Weight of Ongole Crossbred Cattle in Various Age Groups - Erni, Nurliani; Suhardi, Suhardi; Wibowo , Ari; Dinanti, Kirana Dara (AGRITROPICA : Journal of Agricultural Sciences, 2025)
This study aimed to estimate the value of genetic correlation and the regression equation between body weight and body measurements of male Ongole crossbred (PO) cattle across various age groups. The sample used consisted of 80 male PO cattle divided into four age groups: I0 (<18 months), I1 (18 to 24 months), I2 (24 to 30 months), and I3 (>30 months).  The parameters observed include body weight (BW), body length (BL), body height (BH), hip height (HH), and chest circumference (CC). Correlation and regression data were analysed using the Excel program; the regression between body weight and body size was analysed using the best subset regression method. The results showed a strong to robust genetic correlation between body weight and body size, with the highest correlation value in chest circumference (CC) in all age groups (0.92-0.98). The regression equations revealed that chest circumference had the highest regression coefficients (ranging from 2.36 to 3.87), indicating that it is the most reliable body size measurement for predicting body weight in PO cattle. This study concludes that chest circumference can be used as a reliable parameter to estimate the weight of PO cattle in various age groups, especially for farmers who do not have access to scales.